The Effect of Intertemporal Speculation on the Outcomes in Seller Posted Offer Auction Markets - Hoffman, Elizabeth; Plott, Charles R. (Quarterly Journal of Economics, 1981)
This paper extends the experimental examination of posted offer auction markets to a market with intertemporal speculators. Previous experimental results demonstrate that posted offer markets induce inefficiencies, and also an income distribution that works to the disadvantage of those facing posted prices. The results of this paper suggest that these properties of the posted offer institution hold in the presence of intertemporal speculation.